Sustainable recovery plan for an urban-rural community affected by the Fundão Dam disaster in Brazil - Arêdes, Larissa; Senna, Gabriel; Souza, João Vitor; Fonseca, Tayami; Cordeiro, Juni; Fonseca, Maria Thereza; Gomes, Alessandra R.; de Paula, Hugo Luiz Martins; de Souza, Gisela Barcellos; Salgado, Marina; Teixeira, Maria Cristina Villefort; da Costa, Stael Pereira; et al. (Journal of Environmental Engineering and Landscape Management, 2025)
The rupture of Fundão Dam spilled contaminated tailings across the Doce river basin, severely damaging municipalities such as the urban Barra Longa and the rural Gesteira. The wave of tailings led to the sediment deposition in rivers margins, causing the loss of riparian forests and cropping areas. Sediment analyses confirmed the presence of toxic compounds (sodium and ether amine) and a very low fertility. In consequence, there was a sharp decline in agro-pastoral production in Gesteira, leading to land abandonment and rural exodus. In the urban area of Barra Longa, the wave of tailings damaged the urban floodplain and the square, which were rehabilitated using grey infrastructure. Alternatively, we proposed a new landscape recovery plan for both Barra Longa and Gesteira based on Nature and Community-based solutions that contemplate the inclusion of green infrastructure, the remediation of toxic compounds, the restoration of soil fertility, permeability and stabilization, riparian forest rehabilitation and the recovery of agro-pastoral productivity, ultimately aiming at reducing the flood risk and land abandonment.